Gas Chromatographic Analysis of Essential Oil Mixture Using Phenyl-Modified Algirian Bentonite - Aziz Ramadan, Abdul; Mandil, Hasna; Lahmek, Mhammed (Asian Journal of Chemistry, 2011)
A new support was prepared from Algerian bentonite by thermal treatment at 1100 ºC and chemically treated by 6N HCl (diameter range 125-150 μm and the surface area S = 12 m2/g) was grafted by two steps, the first one was a chlorination of the silica surface using dimethyldichlorosilane (BAlgCl) and the second by reacting Grignard reagent with bromophenyl magnesium (BAlgC6H5), S = 13 m2/g. The surface properties of octadecyl-modified bentonite were studied by nitrogen adsorption at 77 K. Distinguish the new support with a good stability at high degrees of temperature which enable its application in gas chromatography. Essential oils' mixtures (a- pinene, b- pinene, cineole, fenchone, borneol and anethole) and some fatty acid (C8, C10, C12, C14 and C16) in standard (GLC-30) using the modified BAlgC6H5 by gas chromatographic analysis were determined. The analytical results were characterized by high precision, accuracy and reproducibility with relative standard deviation not exceeding 2.7 %.